Clinical and molecular characteristics of Wiskott‐Aldrich Syndrome in five unrelated Chinese families. (16th November 2021) - Jiang, Jiali; Zhou, Junli; Wei, Manlv; Singh, Sanjeev; Nikuze, Lauriane; Huang, Lifang; Li, Yuping; Jiang, Jinxia; Wei, Hongying
Abstract: Wiskott‐Aldrich syndrome (WAS) also called the eczema‐thrombocytopenia‐immunodeficiency syndrome is a primary immunodeficiency disease with X‐linked recessive inheritance caused by mutations in the WAS protein (WASp) gene and characterized by thrombocytopenia with reduced platelet volume, eczema, immunodeficiency, and increased risk of malignant tumours. The mutations will lead to separate WAS severity which can be typical severe 'classical' WAS or less severe 'non‐classical' WAS. This article will review and analyse clinical and immune characteristics of five unrelated Chinese families harbouring classical and non‐classical WAS. The expression of WASp was detected in the peripheral blood monocytes (PBMC) by flow cytometry, and five mutations were found by WAS gene sequencing, one of which had not been reported in the literature, namely frameshift mutation c.1240_1247delCCACTCCC (p. P414Sfs*41).